Autologous Bone for the Reconstruction of Skull Defects. Issue 1 (February 2016) - Zhang, Qiujian; Tian, Xuping; Shu, Hansheng; Zhang, Hui; Xuan, Shanjing; Chao, Qing
Abstract : Objective: To restore the normal barriers protecting the intracranial structures and obtain a permanent or very durable reconstruction. Methods: This retrospective study spanning 3 years included 36 patients who underwent reconstruction of skull defects either with autologous bone or with 3-dimensional (3D) titanium mesh. To analyze difference of both, 2 groups (group A 1 group skull defect for reconstruction with 3D titanium mesh, group B the other group with autologous bone) were divided. Results: A favorable surgery outcome was attained in the follow-up without complications in the group B. Osteolysis was not observed from 3D reconstruction of computed tomography (CT) from 3D reconstruction of CT in the group B ( P >0.05). Complications was significantly different, comparing with group A ( P <0.05). General features (age, follow-up) were not different ( P >0.05). Conclusion: Autologous bone for the reconstruction of skull defects seems to be good technique for permanent or very durable reconstruction.